Magnetotelluric study of the Las Cañadas caldera (Tenerife, Canary Islands) : structural and hydrogeological implications - Schnegg, Pierre-André; Heise, Wiebke; Martí, Joan; Muñoz, Gerard; Pous, Jaume; Soriano, Carles (My University, 2002)
The Las Cañadas caldera in Tenerife (Canary Islands) is a well-exposed caldera depression in which the active Teide–Pico Viejo complex stands. In addition to its volcanological interest, the Las Cañadas caldera also holds the main groundwater reservoir of Tenerife. An audiomagnetotelluric and magnetotelluric survey was carried out in order to image the interior of the caldera depression. The field campaign consisted of 33 audiomagnetotelluric sites in the period range from 0.001 to 0.3 s and 11 magnetotelluric sites from 0.004 to 200 s. A detailed mapping of the electrical conductivity of the subsurface was obtained. For the long periods a three-dimensional modelling of the island – including the bathymetry – was carried out to study the effect of the ocean. This effect starts to be important at periods longer than 10 s. Accordingly, the sites were arranged into six profiles and a two-dimensional joint inversion of all data until 10 s was performed for each profile. The geometry of the high conductive zones found indicates that the caldera includes two closed depressions in the western (Ucanca) and central (Guajara) sectors, whereas in the eastern sector (Diego Hernández) the top of the main conductive zone shows a gentle inclination towards the northeast (La Orotava valley). A narrow and marked high conductive anomaly, probably caused by the presence of highly fractured rocks and fossil hydrothermal alteration along a fracture zone, runs parallel and close to the present caldera wall, suggesting the position of the structural border of the caldera. The results indicate that there are two main aquifer zones separated by the Roques de García spur, coinciding with the western and central depressions. The eastern depression could be hydrologically disconnected from the central depression by another structural limit not visible at the surface. The saturation zones would have a thickness of more than 700 m starting at a few hundred metres below the present caldera floor. The data are consistent with a multiple vertical collapse origin for the caldera depression rather than a sector collapse origin.
Keywords: magnetotelluric surveys; hydrogeology; volcanology; Tenerife; Las Cañadas caldera